2020
DOI: 10.1002/ajh.25713
|View full text |Cite
|
Sign up to set email alerts
|

Platelets from Calreticulin mutated essential thrombocythemia patients are less reactive than JAK2 V617F mutated platelets

Abstract: Both JAK2V617F and calreticulin (CALR) mutated essential thrombocythemia (ET) patients have different clinical characteristics, with lower thrombosis risk in patients with CALR mutations. To elucidate the mechanism for this lower risk we studied platelet function in ET patients with either JAK2V617F or a CALR mutation. Platelet activation state was similar in ET and healthy controls at baseline using P‐selectin and PAC1 flow cytometry analysis. However, CALR mutated platelets were significantly less activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Additionally, in an international collaborative study, arterial thrombosis in ET was predicted by age > 60 years, thrombosis history, cardiovascular risk factors including tobacco use, hypertension, diabetes mellitus, leukocytosis >11 × 10 9 /L, JAK2V617F mutation; male gender predicted venous thrombosis, while a lower risk of thrombosis was noted in patients with extreme thrombocytosis greater than a million/μL 18 . Presence of CALR mutation in ET patients confers a lower risk for thrombotic events which may be explained by defects in platelet activation not only in response to ADP stimulation but also impaired interaction with fibrinogen, compared to JAK2 mutated patients or those without MPN 23 …”
Section: Overview Of the Thrombosis Risk In Mpnmentioning
confidence: 94%
See 1 more Smart Citation
“…Additionally, in an international collaborative study, arterial thrombosis in ET was predicted by age > 60 years, thrombosis history, cardiovascular risk factors including tobacco use, hypertension, diabetes mellitus, leukocytosis >11 × 10 9 /L, JAK2V617F mutation; male gender predicted venous thrombosis, while a lower risk of thrombosis was noted in patients with extreme thrombocytosis greater than a million/μL 18 . Presence of CALR mutation in ET patients confers a lower risk for thrombotic events which may be explained by defects in platelet activation not only in response to ADP stimulation but also impaired interaction with fibrinogen, compared to JAK2 mutated patients or those without MPN 23 …”
Section: Overview Of the Thrombosis Risk In Mpnmentioning
confidence: 94%
“…18 Presence of CALR mutation in ET patients confers a lower risk for thrombotic events which may be explained by defects in platelet activation not only in response to ADP stimulation but also impaired interaction with fibrinogen, compared to JAK2 mutated patients or those without MPN. 23 It is to be noted that current thrombotic risk stratification models in MPN have limited applicability in determining pregnancy complications. In this regard, some have suggested classifying pregnant ET patients as low risk in the absence of prior thrombotic events or inherited thrombophilia, age < 35 years, and platelet count less than a million/μL, whereas highest risk was conferred by history of obstetric complications, or maternal thrombosis or hemorrhage, particularly a recent thrombotic event.…”
Section: Overview Of the Thrombosis Risk In Mpnmentioning
confidence: 99%
“…The presence of the JAK2V617F mutation has been associated with an increased risk of thrombosis in ET [34,35], and the mechanism involved enhanced activation of platelets, leukocytes, and endothelial cells as well as prothrombotic soluble factors [36][37][38]. In our overall cohort, JAK2V617F was not associated with kidney dysfunction; however, CALR mutations were significantly less frequent in eGFR3 (Table S1).…”
Section: Driver Mutationsmentioning
confidence: 80%
“…Morphologically unusual platelets with an abnormal function may be observed in CALR-mutated MPNs because thrombopoietin-independent megakaryopoiesis through the thrombopoietin receptor has been reported to be activated by mutant CALR ( 13 ). Another study reported that CALR-mutated platelets were less activated following ADP stimulation ( 14 ). They speculated that the result could explain the lower risk of thrombosis in CALR-mutated ET patients compared with JAK2-mutated ET patients.…”
Section: Discussionmentioning
confidence: 99%